Food industry political practices in Chile: "the economy has always been the main concern" - Mélissa Mialon; Camila Corvalan; Gustavo Cediel; Fernanda Baeza Scagliusi; Marcela Reyes (BMC, 2020)
Abstract Background In the business literature, the term "corporate political activity" (CPA) refers to the political strategies undertaken by corporations to protect or expend their markets, by influencing, directly or indirectly, the policy process. There is evidence that food industry actors use such political practices, which poses a significant threat to public health. Our study objective was to identify the political practices of the food industry in Chile. Results In Chile, food industry actors supported community initiatives, particularly those targeted at children and those focused on environmental sustainability. Food industry actors also funded research through prizes, scholarships, and by supporting scientific events. Food industry actors lobbied against the development and implementation of a front-of-pack nutrition labelling policy, including with support from the Ministries of Economy, Agriculture and Foreign Affairs. Food industry actors, for example, claimed that there would be unintended negative consequences for society and the economy, and that the policy would breach trade agreements. The same arguments were used against a proposed tax increase on sugar-sweetened beverages. Food industry actors stressed their crucial role in the Chilean economy and claimed to be part of the solution in the prevention and control of obesity, with a particular focus on their efforts to reformulate food products, and their support of physical activity initiatives. Interviewees noted that the political influence of the food industry is often facilitated by the neo-liberal and market-driven economy of Chile. Nevertheless, this system was questioned through social protests that started in the country during data collection. Conclusions In Chile, food industry actors used numerous action- and argument-based CPA practices which may influence public health policy, research, and practice. Despite strong influence from the food industry, Chile adopted a front-of-pack nutrition labelling policy. While the country has some measures in place to manage the interactions between government officials or public health professionals, and the industry, there is still a need to develop robust mechanisms to address undue influence from corporations.